The Peached Tortilla : modern Asian comfort food from Tokyo to Texas - Silverstein, Eric (Sterling Epicure, an imprint of Sterling Publishing Co., Inc., 2019)
This is Asian comfort food at its best! Eric Silverstein puts a modern American twist on dishes that are firmly rooted in Asian street food to deliver intensely flavored, soul-satisfying fare. His background in Asian food culture as a child in Japan, and later his immersion in Southern and Southwestern cuisine, influencs his cooking today, at his restaurant, The Peached Tortilla, in Austin, Texas. Silverstein's personal narrative, detailing the difficult but ultimately successful journey from fledgling food truck operator to owner of one of Austin's top restaurants, also weaves in and out of the book and casts an inspiring spell of its own. The 100 flavor-packed recipee include many of The Peached Tortilla's most-beloved dishes, like Silverstein's Banh Mi Taco and Bacon Jam Fries, which gained a cult-like following when he first served them out of his famed Austin-based food truck. Other crowd-pleasing favorites range from crispy Umami Fried Chicken and Korean Short Rib Pappardelle with Smoked Crème Fraîche to Roasted Cauliflower with Nori Brown Butter.